Degradation of aniline: sodium alginate/modified pomelo cellulose double cross-linking system as a bacterial immobilization carrier - Zheng Fan; Zhenzhen Fang; Peng Tao; Laiyun Jin; Guoliang Zhang (Water Science and Technology, 2023)
Pectin cellulose grafted with glycidyltrimethylammoniochloride (GTMAC) was successfully obtained following the processes of depectinfibrillation and cellulose cationization using ordinary Shatian pomelo peel produced in Yongzhou, Hunan, as the raw material. This is the first report on a new type of functionalized sodium alginate-immobilized material prepared from the fibers of pomelo peel. The material was prepared by combining modified pomelo peel cellulose and sodium alginate following the processes of physical and chemical double cross-linking. The prepared material was used to embed the target bacteria to achieve the biodegradation of p-aniline. The concentration of CaCl2 was adjusted when the alginate gelled, and the alginate to yuzu peel cellulose ratio was tuned. The immobilized material-embedded bacteria help achieve the best degradation effect. Bacteria are embedded during the process of the degradation of aniline wastewater, and the functionalization of the cellulose/sodium alginate-immobilized material results in unique surface structure performance. The performance of the prepared system is better than that of the single sodium alginate-based material characterized by a large surface area and good mechanical properties. The degradation efficiency of the system is improved significantly for the cellulose materials, and the prepared materials can potentially find applications in the field of bacteria-fixed technology. HIGHLIGHTS Pomelo peel fiber was extracted for the first time and used in the preparation of immobilized material.; By combining with sodium alginate, the specific surface area of the fixed material can be increased by the pomelo peel fiber with a spiral tube shape and rough surface.; The cationic-modified pomelo peel fiber can improve the mechanical properties and stability of the immobilized material by ionic bonding.;